The Impact of pregnancy and birth-related risk factors on the incidence of developmental dysplasia of the hip in newborns - Patryk Dudek; Klaudia Łuczak; Marcel Chudzikowski; Wiktoria Ulicka; Justyna Pięta; Adrianna Tabeau; Agnieszka Pawlik; Hanna Sitarek; Agata Prokopiuk; Joanna Prus (Journal of Education, Health and Sport)
Introduction: Developmental dysplasia of the hip (DDH) is a multifactorial condition that, if untreated, can lead to long-term complications such as early-onset osteoarthritis and disability. Risk factors, including breech presentation, family history, female sex, firstborn status, high birth weight, and oligohydramnios, are associated with 50–60% of DDH cases. Screening approaches vary, with selective and universal ultrasound strategies in use. This review examines DDH risk factors related to birth and pregnancy, emphasizing the importance of early diagnosis and timely intervention to improve patient outcomes.